Types of Cities of the Trans-Siberian Railway: Dynamics of Population and Industrial Functions - Mironova, M.N.; Kuznetsova, N.G.; Sholudko, A.N. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Ėkonomika, 2017)
The article is devoted to the analysis of changes in industry in different types of cities by the Trans-Siberian Railway (Transsib) in the post-Soviet period. The prevailing types of cities in terms of the current population and the specifics of its dynamics in 1990-2015 are estimated. Key trends in the development of industry are evaluated on the basis of an analysis of the number of closed and newly emerged industrial enterprises and industries in these cities. The interrelation between the dynamics of city-forming industrial enterprises and the change in the population in the cities of the Trans-Siberian during this period was determined. The main regularities of the change of industrial functions in different types of cities are established.